2020
DOI: 10.1186/s12896-020-00606-1
|View full text |Cite
|
Sign up to set email alerts
|

Cassava/peanut intercropping improves soil quality via rhizospheric microbes increased available nitrogen contents

Abstract: Background: Intercropping, an essential cultivation pattern in modern agricultural systems, increases crop yields and soil quality. Cassava and peanut intercropping systems exhibit advantages in solar utilization and cadmium absorption, etc. However, the inner mechanisms need to be elucidated. In this study, Illumina MiSeq platform was used to reveal the rhizospheric microbes and soil quality in cassava/peanut intercropping systems, and the results provided a reference for the application of this method in stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 66 publications
(72 reference statements)
8
34
0
Order By: Relevance
“…DNA was extracted from the soils using the PowerSoil DNA extraction kit (MoBio Laboratories, Inc.) (Fierer et al, 2012). Bacterial and fungal community composition was analyzed based on high‐throughput sequencing as the detailed procedure described in Tang et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from the soils using the PowerSoil DNA extraction kit (MoBio Laboratories, Inc.) (Fierer et al, 2012). Bacterial and fungal community composition was analyzed based on high‐throughput sequencing as the detailed procedure described in Tang et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…On March 10, 2016-2018, sugarcane and peanut were planted simultaneously in the field. Monocropping sugarcane and monocropping peanut systems were used as control, and sugarcane/peanut intercropping system was the treatment group, which contained intercropping sugarcane and intercropping peanut, as previously reported [19]. The experiment was arranged in plots (6 × 8 m) in a randomized design with three replicates in each treatment.…”
Section: Experimental Designmentioning
confidence: 99%
“…The available N, available P, available K, and organic matter contents were measured by the alkaline hydrolysis diffusion method, sodium bicarbonate extraction/Mo-Sb colorimetry, ammonium acetate extraction/flame photometry, and the potassium bichromate titrimetric method, respectively. Catalase activity [22], sucrase activity, proteinase activity, urease activity [23], and acid phosphatase activity [24] were measured by permanganate titration, sodium thiosulfate titration, ninhydrin colorimetry, indophenol blue colorimetry, and the disodium phosphate benzene colorimetric method, respectively [19].…”
Section: Soil Physicochemical Property Analysismentioning
confidence: 99%
“…For example, in wheat-soybean intercropping (Bargaz et al 2017), maize/wheat-faba bean intercropping (Wang et al 2020), millet-mung bean intercropping (Dang et al 2020), and cucumber-cereal intercropping (Li and Wu 2018). Tang et al (2020), observed a higher diversity of both bacterial and fungal species in cassava-peanut intercropping, but also peanut monoculture, suggesting that the leguminous peanut intercrop was responsible for the observed higher soil microbial diversity, a factor we could not correct for in our study. Similarly, Gao et al (2019) observed that peanut monoculture plots had the highest richness and abundance of soil bacteria compared to intercropping tobacco after two and four years.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, the abundance of bene cial soil bacteria was higher in intercropping systems with complete and semi-below ground interactions compared to monoculture systems (Li et al 2018). Tang et al (2020) observed variations in availability of soil minerals and enzymes as a result of intercropping with either peanut or cassava. In the same study, certain bacterial groups including Nitrospirae increased in abundance, and others were associated with improved soil quality.…”
Section: Introductionmentioning
confidence: 86%